Parafibromin, APC, and MIB-1 Are Useful Markers for Distinguishing Parathyroid Carcinomas From Adenomas. Issue 10 (November 2017) - Hosny Mohammed, Kareem; Siddiqui, Momin T.; Willis, Brian C.; Zaharieva Tsvetkova, Dobromira; Mohamed, Amr; Patel, Snehal; Sharma, Jyotirmay; Weber, Collin; Cohen, Cynthia
Abstract : Background: Differentiation of parathyroid carcinoma (PC) from parathyroid adenoma (PA) relies solely on the pathologic determination of invasion of surrounding structures and/or distant metastasis. Parathyroid lesions with atypical histologic features with no demonstration of invasion or metastasis present a diagnostic dilemma. Different authors report a parafibromin and adenomatous polyposis coli ( APC ) loss or reduction in PC cases. High proliferative activity of MIB-1 and increased galectin 3 expression are reported in PC. There is no clear cutoff for the sensitivity, specificity, or predictive value for all these markers. Methods: The immunohistochemical expression of parafibromin, APC, MIB-1, and galectin 3 was studied in 73 adenomas, 21 PCs, and 3 atypical adenomas. The presence or absence of each marker was identified through the use of a comprehensive scoring system based on multiplying the percentage of tumor cells stained (0 to 100) and the staining intensity (0 to 3) on each biopsy. The highest score that any slide could reach was 300. A cutoff of >100 was used to consider the specimen positive for parafibromin, APC, or galectin 3 staining. MIB-1 proliferation indices were calculated using image cytometry; proliferation indices >5% were considered positive. Results: We identified parafibromin loss in 7/21 (33%) carcinomas and 1/73 (1%) adenomas. Loss of APC was seen in 20/21 (95%) carcinomas and 38/73 (52%) adenomas. MIB-1 indices were elevated in 18/21 (86%) carcinomas. MIB-1 indices were <5% in all (100%) adenomas. MIB-1 indices were elevated in 2/3 (67%) atypical adenomas. Conclusions: Our study presents a clear cutoff to determine the practicality of using parafibromin, APC, and MIB-1 as immunohistochemical markers to differentiate between PCs and PAs. Loss of parafibromin and a high MIB-1 index are both independently sensitive and specific markers for the diagnosis of PC. Loss of APC was only specific for PC. This panel of markers provides a novel, useful approach in the diagnosis and differentiation of PCs from PAs.